108 A Multidisciplinary Team Initiative to End PJ Paralysis Was Successful in Achieving Cultural Change on An Acute Geriatric Ward. (16th March 2021) - Butler, J; Welford, T
Abstract: Introduction: Prolonged bedrest amongst the elderly causes deconditioning leading to; increased hospital length of stay, additional social costs and decreased quality of life. An audit on an acute geriatric ward in November 2018, found that over a third of patients medically fit (PMF) to sit out remained in bed all day. Therefore, a service development initiative was undertaken, addressing the misconception that keeping elderly patients in bed is safe, when in fact, unintentional harm results. Method: In a root cause analysis, four main reasons for bedrest were identified: risk aversion, unknown function, widespread "bed is safe" culture and lack of equipment. The project tasked getting PMF out of bed each day and was audited daily from November 2018 to present, involving all members of the multi-disciplinary team (MDT) and using a "plan, do, study, act" approach. Results: Initially, the project showed an increase in percentage of PMF sitting out each day, but this subsequently decreased with winter pressures. However, for a whole year (February 2019–February 2020) a sustained and significant improvement was achieved (64.3%–89.7%). The pre-COVID19 period (February–March 2020) saw fluctuations in PMF sitting out. Data collection halted during the COVID19 peak, although observationally most patients remained in bed. Auditing resumed from June 2020 (COVID19 recovery phase) which showed a steady increase in PMF out of bed, with recent figures surpassing pre-COVID19 levels (97.8%). Conclusion: Cultural change takes time to embed and needs persistent reviewing by a dedicated and engaged MDT. Improvements were made through more accessible doctor's advice, better MDT education and communication, daily feedback of data and sourcing additional equipment. Disruption to working patterns over the COVID19 period made this unachievable and the project lost impetus. In the COVID19 recovery phase, the specialized MDT reformed and worked successfully to restore the cultural change as evidenced by audited data.